SO3 formation and the effect of fly ash in a bubbling fluidised bed under oxy-fuel combustion conditions - Sarbassov, Yerbol; Duan, Lunbo; Jeremias, Michal; Manovic, Vasilije; Anthony, Edward J. (Elsevier, 2017)
This study investigates the formation of SO3 under air and oxy-fuel combustion environments in a bench-scale bubbling fluidized bed. Flue gas compositions typical of air and oxy-fuel environments were simulated by bottle gases. Parameters such as bed temperature, SO2, O2 and H2O concentrations were varied to determine their effect on the formation of SO3 in both tests with fly ash acting as a catalyst catalyzed and uncatalyzed tests. Catalytic tests were conducted by adding three different fly ashes generated from three different coals. Experimental results support the expectation of show increased SO3 concentration for oxy-fuel combustion environments compared to typical air-fired environments. SO3 concentrations increased with combustion temperature, O2 and H2O concentrations. Catalytic tests have shownshowed that the formation of SO3 depends on the chemical composition of the fly ash, while unburnt carbons in the ash tend to reduce SO3 concentrations.
Keywords: SO3 formation; Catalysis; Oxy-fuel combustion; Fluidised bed